Repeated loss of consciousness as the first symptom of recurrence of head and neck malignancy: a case report. Issue 1 (4th January 2021) - Funabashi, Sayaka; Yamagata, Kenichiro; Nishii, Tatsuya; Kusano, Kengo
Abstract: Background: Head and neck malignancies rarely cause reflex syncope. Three mechanistic patterns of reflex syncope are known in such patients: carotid sinus syndrome, glossopharyngeal neuralgia syndrome, and parapharyngeal space lesions syncope syndrome. There are few reports describing parapharyngeal space lesions syncope syndrome. Case summary: A 61-year-old man with a history of head and neck cancer underwent left lingual resection and left anterior cervical lymph node dissection followed by chemoradiotherapy. Two months later, he experienced his first syncope and was admitted to our hospital for further investigation. During the first few days in the hospital, he experienced loss of consciousness. Carotid artery massage and cervical rotation-extension examinations revealed no abnormalities, and glossopharyngeal neuralgia was not observed. Cervical computed tomography showed recurrence of tongue cancer infiltrating the para-nasopharyngeal space. Consequently, the patient had sinus pause during the loss of consciousness; hence, we suspected parapharyngeal space lesions syncope syndrome. Pacemaker implantation was considered but could not be performed as the patient passed away because of the original malignancy. Discussion: Parapharyngeal space tumours are often characterized by the absence of subjective symptoms, although symptoms such as neck swelling and discomfort in the throat have been reported. Parapharyngeal space lesions syncope syndrome is caused by tumour invasion into the parapharyngeal space, and there is no known trigger for syncope. Our case is unique because the patient's first symptom of recurrence of tongue cancer infiltrating the para-nasopharyngeal space was repeated loss of consciousness.